Motivation and study engagement: a study of Muslim undergraduates in Malaysia - Hassan, Arif; Al-Jubari, Ibrahim (Universiti Putra Malaysia Press, 2016)
There has always been a serious concern about students’ academic performance in schools and institutions of higher learning. Mostly, it has been seen in terms of lack of motivation. However, little attention has been given to the reasons for poor motivation. The SelfDetermination Theory (SDT) of motivation provides a new perspective on motivation. This paper investigates students’ motivation and study engagement using the SDT framework. It examines the role of learning climate, intrinsic motivation resulting from basic needs satisfaction, self-perception of choice and self-awareness of students’ study engagement. This study attempts to validate SDT propositions on students’ motivation and study engagement in the Asian context and within an Islamic institution of higher education. Data were collected from 432 undergraduate students (Females = 62.2%) representing several study disciplines. Standardised instruments were employed to measure the constructs of learning climate, basic needs, perceived self-determination and study engagement. Results provided strong support for the SDT propositions suggesting that an autonomy supportive learning climate significantly contributed to intrinsic need satisfaction of autonomy, competence and relatedness. It was also found that the autonomy supportive learning climate and satisfaction of competency need contributed to greater study engagement. This study provides good empirical support to the SDT propositions from a non-Western cultural context.